2010
DOI: 10.2337/dc09-1766
|View full text |Cite
|
Sign up to set email alerts
|

Programming of Adiposity in Offspring of Mothers With Type 1 Diabetes at Age 7 Years

Abstract: OBJECTIVEThe goals of this study were to examine the influence of maternal type 1 diabetes during pregnancy on offspring adiposity and glucose tolerance at age 7 years and to assess whether metabolic factors at birth (neonatal leptin and insulin) predict adverse outcomes.RESEARCH DESIGN AND METHODSWe examined 100 offspring of mothers with type 1 diabetes (OT1DM) and 45 offspring of control mothers. Mothers had previously been recruited during pregnancy, and, where possible, birth weight, umbilical cord insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 22 publications
4
72
0
Order By: Relevance
“…Two additional studies were identified through a search of forward citations [15,48] and four [49][50][51][52] from hand-searching the reference lists of included papers, giving 34 papers in total. Five cohorts were reported in more than one paper, so only the study that reported the outcomes at an age closest to the overall median age of all studies (7 years) was included in the meta-analysis; 10 papers were excluded on this basis [25, 35, 36, 38-40, 42, 47-49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional studies were identified through a search of forward citations [15,48] and four [49][50][51][52] from hand-searching the reference lists of included papers, giving 34 papers in total. Five cohorts were reported in more than one paper, so only the study that reported the outcomes at an age closest to the overall median age of all studies (7 years) was included in the meta-analysis; 10 papers were excluded on this basis [25, 35, 36, 38-40, 42, 47-49].…”
Section: Resultsmentioning
confidence: 99%
“…Included studies n=9 Three studies adjust for covariates including maternal prepregnancy BMI [15,27,46]. A meta-analysis of the raw BMI z score data from these three studies shows increased BMI in the offspring of diabetic mothers (0.23 [95% CI 0.06, 0.40]; p=0.009; I 2 =20%, p=0.29).…”
Section: Data Received N=2mentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers mentioned BP, but reported no data [26,41]; the authors were contacted, but were unable to provide the data. Where outcome data were not represented as unadjusted mean and SD [24,30,33,34,36,38,42], the authors were contacted; data were received for all studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…1). Three additional studies [40][41][42] were identified from the reference lists of included papers, giving 22 papers in total. Two cohorts were reported twice; two papers were excluded on this basis [35,37].…”
Section: Literature Searchmentioning
confidence: 99%